Classification of hand eczema. (15th September 2015) - Agner, T.; Aalto‐Korte, K.; Andersen, K.E.; Foti, C.; Gimenéz‐Arnau, A.; Goncalo, M.; Goossens, A.; Le Coz, C.; Diepgen, T.L.; ,
Abstract: Background: Classification of hand eczema (HE) is mandatory in epidemiological and clinical studies, and also important in clinical work. Objectives: The aim was to test a recently proposed classification system of HE in clinical practice in a prospective multicentre study. Methods: Patients were recruited from nine different tertiary referral centres. All patients underwent examination by specialists in dermatology and were checked using relevant allergy testing. Patients were classified into one of the six diagnostic subgroups of HE: allergic contact dermatitis, irritant contact dermatitis, atopic HE, protein contact dermatitis/contact urticaria, hyperkeratotic endogenous eczema and vesicular endogenous eczema, respectively. An additional diagnosis was given if symptoms indicated that factors additional to the main diagnosis were of importance for the disease. Results: Four hundred and twenty‐seven patients were included, 379 (89%) of the patients could be classified directly into one of the six diagnostic subgroups, with irritant and allergic contact dermatitis comprising 249 patients (58%). For 32 (7%) more than one of the six diagnostic subgroups had been formulated as a main diagnosis, and 16 (4%) could not be classified. 38% had one additional diagnosis and 26% had two or more additional diagnoses. Eczema on feet was found in 30% of the patients, statistically significantly more frequently associated with hyperkeratotic and vesicular endogenous eczema. Conclusion: We find that the classification system investigated in the present study was useful, being able to give an appropriate main diagnosis for 89% of HE patients, and for another 7% when using two main diagnoses. The fact that more than half of the patients had one or more additional diagnoses illustrates that HE is a multifactorial disease.